The application of the data envelopment analysis method in investigating the performance of irrigated wheat producers with an environmental approach - Fatemeh Zargaran; Mahmoud Daneshvar Kakhki; Leili Abolhassani; Elnaz Nejatiyanpour; Mahmoud Sabouhi Sabouni (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: In this study, the technical efficiency and environmental efficiency of irrigated wheat producers in 31 provinces of the country were investigated by considering the emission of CO2 as an undesirable output during the years 1385-1397.Methodology: Data envelopment analysis and the Malmquist productivity index were used under natural disposability and managerial disposability. In the Malmquist index, the amount of wheat production was used as the desired output, and the amount of carbon dioxide emission from the production of irrigated wheat was used as the undesirable output. To determine the amount of CO2 emission, the carbon dioxide emission coefficients related to each production input and the amount of their use in the study area were used.Findings: The results of the Malmquist productivity index with the absence of border crossing showed that under the natural disposability, Khorasan-Razavi has the highest index value. Kermanshah province has strong efficiency, and Fars has weak technical efficiency in irrigated wheat cultivation. Also, the results under managerial disposability showed that East Azerbaijan has the highest efficiency. Ardabil, Bushehr, Fars, Kermanshah, and Hormozgan, with ten years of Malmquist productivity index more than one, East Azerbaijan, West Azerbaijan, Chaharmahal and Bakhtiari, North Khorasan, Kurdistan, and Lorestan had a six-year history of Malmquist productivity index less than one. The results of Malmquist's productivity index with the occurrence of border crossing show that under natural disposability, this index is more than one in all provinces. It is, although, under managerial disposability, less than one in all provinces.Originality/Value: It is recommended that farmers' knowledge and awareness of the side effects of irrigated wheat production on the environment be increased through training courses and classes. Considering the climate change, the provinces that have more environmental efficiency in the production of irrigated wheat should be prioritized for cultivation.